2009
DOI: 10.1183/09031936.00035309
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of tuberculosis in an Eastern-Asian country with an extreme continental climate

Abstract: Aggregate monthly notifications of incident sputum smear-positive tuberculosis (TB) in Mongolia, stratified by sex and age groups, were analysed separately for Ulaanbaatar, Mongolia, and the rest of the country for the 9-yr period from 1998 to 2006. TB notifications were compared with ambient surface temperature.More than twice as many TB cases were notified in the peak month (April) compared with the trough months (October-December), paralleling the temperature curve. The fluctuations recurred consistently ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
55
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 12 publications
12
55
0
Order By: Relevance
“…The spring peak month was similar to the results from many other studies conducted in the northern hemisphere including those in India [10], Spain [11], Mongolia [12], China [13], the USA [14], Portugal [15], and the Netherlands [16]. The peak TB notification in South Africa [17] and Australia [18] was in October, which is the month of local spring in the southern hemisphere.…”
Section: Discussionsupporting
confidence: 88%
“…The spring peak month was similar to the results from many other studies conducted in the northern hemisphere including those in India [10], Spain [11], Mongolia [12], China [13], the USA [14], Portugal [15], and the Netherlands [16]. The peak TB notification in South Africa [17] and Australia [18] was in October, which is the month of local spring in the southern hemisphere.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to Wuhan (Fig. 7a,b), spring peaks of SSP and SSN pulmonary TB epidemics have been observed in other countries and regions, including North India [4], Spain [5], Ciskei of Central Africa [6], Kuwait [7], Japan [8], South Africa [9] and Mongolia [10]. Regarding the cause of the spring peak of TB epidemics in Wuhan (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have found that the seasonality of TB epidemics is highest in spring in some locations [4][5][6][7][8][9][10]. One dominant hypothesis for the cause of a spring peak in TB epidemics is that an increase in the active mass in poorly ventilated and humid rooms facilitates TB transmission [11].…”
Section: Introductionmentioning
confidence: 98%
“…There were some retrospective studies on the seasonality and trend analysis of TB data to describe the trends of TB incidence [9,10,11,12]. In many countries, various models have been used to forecast TB in order to figure out the trends and predict the root cause of the TB incidence epidemic [13,14,15].…”
Section: Introductionmentioning
confidence: 99%